Where young people with multiple sexual partners seek medical care: implications for screening for chlamydial infection. Issue 6 (December 1998) - Dickson, N; Paul, C; Herbison, P
Abstract : OBJECTIVE: To investigate among young people the relation between the number of sexual partners and use of medical services in order to guide planning of sexually transmitted disease screening. DESIGN: Cross sectional study within a birth cohort using a questionnaire presented by computer. SETTING: Dunedin, New Zealand in 1993-4. SUBJECTS: 477 men and 458 women aged 21 enrolled in the Dunedin Multidisciplinary Health and Development Study, comprising 91.7% of survivors of the cohort. RESULTS: Men with multiple sexual partners in the previous year were less likely to have a general practitioner than men with one or no partners (76.2% v 88.5%, p < 0.01). Among the women the respective proportions (83.1% and 88.4%) were not significantly different. Significantly more women than men (75.8% v 50.7%, p = 0.03) with five or more partners in the previous year had visited their own general practitioner over that period. Among the sexually experienced, more women than men attended any setting appropriate for sexually transmitted disease screening (93.6% v 71.6%, p < 0.001). CONCLUSIONS: In New Zealand a screening programme for sexually transmitted diseases among young adults reliant on invitation by their own general practitioner would be biased towards those at less risk. Opportunistic screening in general practice would potentially include only about half the most sexually active men and three quarters of such women over a 12 month period. The extension of opportunistic screening to other settings considered appropriate for discussion of sexual health issues could potentially engage the vast majority of women, but not men, at most risk. Any screening programme should incorporate an effective method of finding and treating the sexual partners of infected women.